1979
DOI: 10.1139/y79-131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcohol on thermal balance of man in cold water

Abstract: The effects of alcohol on core cooling rates (rectal and tympanic), skin temperatures, and metabolic rate were determined for 10 subjects rendered hypothermic by immersion for 45 min in 10 degrees C water. Experiments were duplicated with and without a 20-min period of exercise at the beginning of cold water immersion. Measurements were continued during rewarming in a hot bath. With blood alcohol concentrations averaging 82 mg 100 mL-1, core cooling rates and changes in skin temperatures were insignificantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…As with alcohol, they may also lead to faulty decision making. 77,81,82 Body Size and Composition. Body fat and muscle mass appear to be instrumental in providing protection for maintaining core body temperature with exposure to cold air and water.…”
Section: Nonenvironmental Risk Factorsmentioning
confidence: 99%
“…As with alcohol, they may also lead to faulty decision making. 77,81,82 Body Size and Composition. Body fat and muscle mass appear to be instrumental in providing protection for maintaining core body temperature with exposure to cold air and water.…”
Section: Nonenvironmental Risk Factorsmentioning
confidence: 99%
“…3). Similarly, no increase was noted in Tsk of the rat at Ta 18-26 °C following acute administration of 1-1.5 g ethanol/kg [22,23], Recent studies in humans, also show no increase in heat loss following acute administration of ethanol and exposure to either thermoneutral [20] or cold Ta [2,9,16,19]. Thus, it seems unlikely that the decrease in Tco in the mammal fol lowing acute administration of 3 g ethanol/kg is due to an increase in peripheral heat loss.…”
Section: Discussionmentioning
confidence: 98%
“…Early investigators noted an increase in peripheral vasodilation and suggested an increase in heat loss accompanied acute ad ministration of ethanol [5,12,13,17,36], However, a number of other reports indicates that there is little change in total body heat loss from man following intake of ethanol at either cold [2,9,14,25] or neutral Ta [20].…”
mentioning
confidence: 99%
“…Several studies have also shown that moderate doses of alcohol (blood alcohol levels of 50-100 mg/dL) can affect the thermoregulation during a cold exposure (17,45,54).…”
Section: Nonthermal Factorsmentioning
confidence: 99%
“…However, in colder water (<28˚C), it has been shown to reduce the metabolic heat production by 10-20% with no significant increase in the core cooling rate (17,54).…”
Section: Nonthermal Factorsmentioning
confidence: 99%